Draft Annual Plan 1988-89 Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1988)
As mentioned in the Introductory note, this Union Territory is predominantly tribal area comprising of 80% Scheduled Castes and Scheduled Tribes population. The mobilisation of additional resources is, therefore limited since the Territory is required to be further developed.
Union Territory of Dadra and Nagar Haveli, Planning Division Administration